Hypermethylation of the CpG-island near the C9orf72 G4C2-repeat expansion in FTLD patients - Xi, Zhengrui (2014)
The G4C2-repeat expansion in C9orf72 is a common cause of frontotemporal lobar degeneration (FTLD) and amyotrophic lateral sclerosis (ALS). C9orf72 transcription is reduced in expansion carriers implicating haploinsufficiency as one of the disease mechanisms. Indeed, our recent ALS study revealed that the expansion was associated with hypermethylation of theCpG-island (5′of the repeat) inDNAsamples obtained from different tissues (blood, brain and spinal cord). However, the link between FTLD and methylation of the CpG-island is unknown. Hence, we investigated the methylation profile of the same CpG-island by bisulfite sequencing of DNA obtained from blood of 34 FTLD expansion carriers, 166 FTLD non-carriers and 103 controls. Methylation levelwassignificantly higher inFTLDexpansion carriers than non-carriers (P 5 7.8E213). Ourresults were confirmed by two methods (HhaI-assay and sequencing of cloned bisulfite PCR products). Hypermethylation occurred only in carriers of an allele with >50 repeats, and was not detected in non-carriers or individuals with an intermediate allele (22-43 repeats). As expected, the position/number of methylated CpGs was concordant between the sense and anti-sense DNA strand, suggesting that it is a stable epigenetic modification. Analysis of the combined ALS and FTLD datasets (82 expansion carriers) revealed that the degree of methylation of the entire CpG-island or contribution of specific CpGs (n 5 26) is similar in both syndromes, with a trend towards a higher proportion of ALS patients with a high methylation level (P 5 0.09). In conclusion, we demonstrated that hypermethylation of the CpG-island 5′of the G4C2-repeat is expansion-specific, but not syndrome-specific (ALS versus FTLD).